A Qualitative Study on the Implementation of Jigsaw Model Cooperative Learning Strategies in Teaching Descriptive Texts at Senior High School: Challenges and Peer Interactions - Rahmi; Muhammad Tahir; Andi Anto Patak (Universitas Islam Negeri Palopo, 2025)
This study investigated the implementation and effects of the Jigsaw model cooperative learning strategy in teaching descriptive text writing to students at Senior High School, particularly in the post-COVID- 19 pandemic context. The research aimed to explore how teachers utilize the Jigsaw method, identify the challenges they face, and analyze how peer interactions contribute to improved descriptive writing skills. A qualitative descriptive research design was employed, utilizing observation checklists, interview guides, and document analysis for data collection. The study involved one English teacher and 33 students from class XI-G at Senior High School. Findings indicate that teachers successfully applied the Jigsaw method by forming diverse groups, providing clear instructions, and closely monitoring group discussions. Despite challenges such as managing group dynamics, encouraging passive student participation, and time constraints, observable improvements in students' writing abilities were noted. Active peer interactions, including idea sharing, collaborative efforts, and constructive criticism, significantly reinforced students' comprehension of text structures and motivated them to write better. Comprehensive assessment rubrics, evaluating grammar, substance, coherence, and structural adherence, confirmed gains in writing quality. The study concludes that the Jigsaw approach effectively fosters students' comprehension and growth in descriptive writing. Teachers plan to continue using this strategy, especially for introducing new content. The theoretical underpinnings of cooperative learning (Aronson, 1978; Johnson S Johnson, 1999, 2009) and social constructivism (Bruner, 1996) provide a robust framework for understanding how the Jigsaw model, through student cooperation, aids in overcoming challenges and enhancing descriptive writing abilities within a safe and stimulating learning environment, ultimately improving academic performance and critical communication skills.